MONOTORING, AUDITOR CHANGE, CHANGE IN DIRECTOR, CEO DUALITY, DAN POLITICAL CONNECTION (PERSEPSI FRAUD HEXAGON) TERHADAP FRAUDULENT FINANCIAL REPORTING PT. GARUDA INDONESIA (PERSERO) TBK. YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2022 - Munawarah, Israfil; Fadillah, M. Khaerul (Jurnal Gici Jurnal Keuangan dan Bisnis, 2024)
ineffectiveness monitoring, auditor change, change in director, ceo duality, and political connection on fraudulent financial reporting of PT. Garuda Indonesia (Persero) Tbk. The type of research used is quantitative associative with research methods in the form of collecting data on the financial statements of PT. Garuda Indonesia (Persero) Tbk. period 2018-2022. The results of the regression test showed that 84.7% while the remaining 15.3% was explained by other factors not examined in this study. While the results of the F test simultaneously show the variables financial stability, ineffectiveness monitoring, auditor change, change in director, ceo duality and political connection together have a significant effect on fraudulent financial reporting. The results of the T test show that the financial stability variable shows no significant effect partially, the ineffectivity monitoring variable shows a partial significant effect, the auditor change variable partially shows no significant effect, the change in director variable partially shows a significant effect, the CEO duality variable partially shows no has a significant effect, and the political connection variable shows that partially it has no significant effect on fraudulent financial reporting